(untitled) (Research, Society and Development, 2020)
Objective: The present study carried out a bibliographic analysis on the doctor-patient relationship in primary health care. Methodology: A systematic review was carried out using descriptors determined based on the Health Sciences Descriptors (DeCS) platform, also employing combinations of Boolean operators. The Virtual Health Library, using the Scielo, LILACS and MEDLINE databases, was used to search for articles published between 2016 and 2020, selected after applying inclusion and exclusion criteria. Results and Discussion: The search gathered a total of 340 articles, which, after reading their title and summary, as well as applying the inclusion and exclusion criteria, 13 papers were selected and analyzed in this study. It was observed that the curriculum of some medical courses is not adequately preparing the student to work in primary care, lacking to develop students an empathic care. In already working professionals, it is still possible to notice the predominance of the biomedical model, where the focus is not on the patient and he does not actively participate in his therapeutic process. Conclusion: This study revealed that higher education institutions should pay more attention to the training of professionals able to work in primary care. In addition, it is noted that many students and doctors who work at ABS do not recognize the patient as being able to take care of their own health. Thus, it is important to carry out further studies to better understand the theme and promote a consensual discussion on the subject.